Oversea Investment Inflows and Trade Policies in Sub-Saharan African Countries - Erhijakpor, A.E.O; Moemeke, S.E; Agbogun, Oghenekparobo Ernest (International Journal of Multidisciplinary Approach Research and Science, 2024)
The paper ascertained the dynamic linkage between overseas investment (Foreign direct investment-FDI & Foreign Portfolio Investment-FPI) inflows and trade openness with emphasis on the SSA Economy. The regressor is overseas investment while the regressed is trade policy measured by trade openness. The study adopted the longitudinal research design. The paper collated data from the World Bank data base, 2021. Specifically, the study sampled 30 SSA countries out of the 48 countries in SSA over the reviewed period of 1992 to 2021. Meanwhile, the study adopted the Robust panel Regression (Panel Corrected Standard Error). The study reported that, FDI inflows has a positive (coefficient value =0.977169) yet significant effect (prob. value = 0.0007<0.05) on trade openness. By implication, FDI inflows are a major predictor of trade openness. In like manner, exchange rate has a positive significant effect on trade openness. However, FPI inflows has a positive (coefficient value = 0.005328) yet insignificant effect (prob. value = 0.7399>0.05). By implication, FPI inflows have direct yet minimal effect on trade openness.  Similarly, high INFR dissuade foreign investors from investing in the economy. On the overall outcomes of the paper conform to cross-country analysis. Hence, the paper concludes that, foreign direct investment is a major overseas investment predictor which causes the SSA economy to be more open to trade. Premised on this, the paper submits that, government agencies and other relevant stakeholders in the SSA economy need to collaborate put in place flexible regulatory laws that guarantee the flows of more foreign direct capital investment into the SSA economy. The study developed a robust economic policy model for African economic policy makers desiring to improve the economic development of their economies through oversea investment inflows and trade openness. The model thus confirmed that, if policies are targeted at addressing the counter-productive effect of inflation and exchange rate interaction on both overseas investment inflows and trade openness, the African economy would be highly developed.